"It's because of community meeting:" toward a responsive reconceptualization of social emotional learning. Issue 2 (15th March 2023) - Stephens, Georgina
ABSTRACT: Exclusionary discipline disproportionally impacts low-income students of Color. Social-Emotional Learning (SEL) offers a promising framework for reducing the use of suspensions in school. Prominent SEL literature and praxis, however, seem to assume a colorblind stance that neglects to respond to the sociocultural and political realities low-income students of Color experience. This action research inquiry evaluates the impact of an SEL program implemented in the third grade of a low-income, urban school serving children of Color. Students and teachers co-created a program grounded in critical and culturally relevant pedagogies, Black ethic of care, Freirean radical love, and restorative justice practices. This inquiry offers policy implications that might enable educators to further expand the development and enactment of similar responsive SEL programs.